A bioarchaeological study of osteoarthritis among populations of northern China and Mongolia during the Bronze Age to Iron Age transition to nomadic pastoralism. (16th June 2016) - Eng, Jacqueline T.
Abstract: This paper examines data on joint disease among archaeological populations of several sites within northern China and Mongolia to test hypotheses about cultural uniformity among pastoralists and potential changes in the levels and types of activities during the Bronze Age to early Iron Age transition from mixed economies to mounted pastoralism. Despite continuing debate on the etiology of osteoarthritis, there is general consensus that joint use is an important contributor to joint disease. The vertebrae and major limb joints (shoulder, elbow, wrist/hand, hip, knee, and ankle/foot) of adult samples from these two periods were analyzed for prevalence and patterns of joint disease with respect to sex, age, time period, and location. There were only two joint regions with a significant difference between males and females: at the elbow, where males had a higher prevalence, and at the hip, where it was higher among females. The findings indicated a positive relationship between age and osteoarthritis, and that the spine was one of the most affected areas, along with the elbow and knee. Between the two time periods, while not at the level of significance, there was a pattern of higher prevalence of osteoarthritis in the vertebrae and upper limb joints among the Iron Age sample, while the Bronze Age sample had higher rates within the lower limb joints. These findings suggest different mechanical stresses between the two periods, perhaps associated with changes from mobility by foot in the Bronze Age to increased mounted mobility during the Iron Age, including mounted warfare. However, when comparing the individual sites within the two periods and within geographic regions, there was no distinct pattern, as there was much variation within both the Bronze Age and the Iron Age sites, as well as within regions. These varied results among sites and regions suggest that were was no uniform pastoral way of life or movement that imprinted clear patterns of osteoarthritis among pastoral samples. Instead, these data suggest that varied activities, movements, and perhaps mixed economic practices and workload among the sexes may have been characteristic among the "pastoral" groups of the Inner Asian steppe.